Kanyouku Asobi: Media Alternatif Belajar Kanyouku dan Budaya Jepang - Isti Khomsah; Dyah Prasetiani; Lispridona Diner (Mezurashii: Journal of Japanese Studies, 2026)
Based on the results of the questionnaire on students of the Japanese Language Education study program, Semarang State University, it was found that idioms were considered difficult. In contrast, interest in learning idioms was quite high by students. Therefore, the researcher developed an alternative learning media in the form of a board game called Kanyouku Asobi that has material in the form of idioms and Japanese culture to overcome the difficulty of learning idioms to make the learning process enjoyable. This study uses a qualitative descriptive approach and aims to describe students` responses and impressions in using Kanyouku Asobi. Primary data in this study were obtained using questionnaire techniques and direct observation, and documentation as secondary data. The questionnaire used in this study was a mixed questionnaire with a Likert scale to determine the accumulation of responses and overall impressions from students in using the media. Direct observation was carried out to strengthen the results of the questionnaire. Documentation was also carried out to record and complete the results of observations so that they can provide real evidence of the research results. Data analysis used qualitative descriptive techniques. The results of the questionnaire showed a percentage of 91% on the indicator of the benefits of learning media and 88% on the indicator of the impression of using learning media. Based on the Likert scale index, it was concluded that the response and impression of students in using Kanyouku Asobi as an alternative to learning Japanese idioms and culture were good.